Kedahsyatan Sholawat Kepada Nabi Muhammad saw - Samsuddin Kade; St. Johariah (Universitas Muslim Indonesia, 2022)
The activity of praying, saying salawat, sending salawat – whatever the term and in any form – to the Prophet Muhammad saw. is a hereditary habit. This is the most enduring habit and is always updated from generation to generation throughout the world where Muslims are located. How come? This activity was initiated and exemplified by the Creator and Ruler of this universe along with the Angels and then it is obligatory on all believers as in the word of Allah swt. Q.S:33/al-Ahzab:56.Salawat is also a form of expression of love for the Prophet. A collection of hadiths has also strengthened this command to pray in various forms of motivation to pray. This is proof of the noble position of the Prophet Muhammad. with Allah and among all existing creatures. This article will describe the issues that are considered relevant to this discussion, namely the Power of Salawat to the Messenger of Allah. includes the definition of salawat, the arguments and information related to salawat, the pronunciation of salawat from the Prophet and the Sufis as well as the benefits and virtues of salawat. The last is the influence of salawat in the life of a Muslim which is the cause of getting heaven in the hereafter.